2021
DOI: 10.1371/journal.pone.0251055
|View full text |Cite
|
Sign up to set email alerts
|

Lower beta cell yield from donor pancreases after controlled circulatory death prevented by shortening acirculatory warm ischemia time and by using IGL-1 cold preservation solution

Abstract: Organs from donors after controlled circulatory death (DCD III) exhibit a higher risk for graft dysfunction due to an initial period of warm ischemia. This procurement condition can also affect the yield of beta cells in islet isolates from donor pancreases, and hence their use for transplantation. The present study uses data collected and generated by our Beta Cell Bank to compare the number of beta cells in isolates from DCD III (n = 141) with that from donors after brain death (DBD, n = 609), before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
1
9
1
Order By: Relevance
“…In three small studies concerning islet isolation from DCD donors, no significant differences in islet yield obtained from DCD compared with DBD pancreases were reported [ 43 , 44 , 45 ]. However, two more recent studies reported a reduction of up to 100 000 IEQ from DCD pancreases compared with DBD pancreases [ 10 , 11 ], and another study reporting a 30% lower yield for DCD pancreases when calculated as beta‐cell number [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In three small studies concerning islet isolation from DCD donors, no significant differences in islet yield obtained from DCD compared with DBD pancreases were reported [ 43 , 44 , 45 ]. However, two more recent studies reported a reduction of up to 100 000 IEQ from DCD pancreases compared with DBD pancreases [ 10 , 11 ], and another study reporting a 30% lower yield for DCD pancreases when calculated as beta‐cell number [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A rapid sterno-laparotomy is then performed followed by cold flush, topical cooling, and procurement of the pancreas. Because of its beneficial effect on DCD pancreas preservation for islet cell isolation 13 , IGL-1 is used as cold preservation solution in our DCD V procurement. Total WIT is defined as time between end-of-life therapy and abdominal aorta cannulation initiating cold preservation.…”
Section: Methodsmentioning
confidence: 99%
“…Between January 2015 and December 2020, 13 DCD V organs that matched our set criteria were processed and included for analysis. They were compared with our reference cohort of 234 donors after brain death (DBD) from the same time period and a cohort of 29 DCD III (donors after controlled circulatory death) organs selected for acirculatory WIT <10 min and IGL-1 preservation solution, conditions that have been shown to favor DCD islet cell isolation 13 . Reasons for euthanasia request are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that induction of plasma Cpeptide-positivity required minimally 2.10 6 cultured beta cells/ kg recipient bodyweight (BW) at minimally 20 percent purity. 2 We choose beta cell number instead of islet equivalents (IEQ) because it directly and specifically expresses beta cell mass while dithizonestaining for IEQ measurement is not beta cell-specific and weakens following culture; the corresponding IEQ can be estimated with a conversion factor of 450 beta cells/IEQ which is taken from prior studies where both parameters were measured 7,8 (Table 1). Donors were ABO-compatible and passed a leucocyte crossmatch but were not human leucocyte antigen (HLA)-matched; they were negative for HIV, hepatitis B and C.…”
Section: Preparation Of Human Islet Cell Graftsmentioning
confidence: 99%